2013
DOI: 10.1371/journal.pone.0083673
|View full text |Cite
|
Sign up to set email alerts
|

ERBB2 in Cat Mammary Neoplasias Disclosed a Positive Correlation between RNA and Protein Low Expression Levels: A Model for erbB-2 Negative Human Breast Cancer

Abstract: Human ERBB2 is a proto-oncogene that codes for the erbB-2 epithelial growth factor receptor. In human breast cancer (HBC), erbB-2 protein overexpression has been repeatedly correlated with poor prognosis. In more recent works, underexpression of this gene has been described in HBC. Moreover, it is also recognised that oncogenes that are commonly amplified or deleted encompass point mutations, and some of these are associated with HBC. In cat mammary lesions (CMLs), the overexpression of ERBB2 (27%–59.6%) has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 80 publications
3
37
1
Order By: Relevance
“…In this context, the association found between elevated serum CTLA-4 and HER2-positive tumors would seem paradoxical, as this subtype is frequently associated with more aggressive features and poorer prognosis in humans. However, a recent study reported a positive correlation between higher HER2 mRNA levels and better clinical outcome in feline mammary carcinoma 25 , while a study using a mouse model of HER2 positive breast cancer found that induced intratumoral expression of a CTLA-4 monoclonal antibody not only failed to exert anti-tumor effects, but instead stimulated tumor growth 26 , in support of our results.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, the association found between elevated serum CTLA-4 and HER2-positive tumors would seem paradoxical, as this subtype is frequently associated with more aggressive features and poorer prognosis in humans. However, a recent study reported a positive correlation between higher HER2 mRNA levels and better clinical outcome in feline mammary carcinoma 25 , while a study using a mouse model of HER2 positive breast cancer found that induced intratumoral expression of a CTLA-4 monoclonal antibody not only failed to exert anti-tumor effects, but instead stimulated tumor growth 26 , in support of our results.…”
Section: Discussionsupporting
confidence: 91%
“…21 However, a recent report claimed that fHER2 overexpression is associated with feline tumors that show nonmalignant features. 35 Our findings support these results, since mammary tumors with Ki-67 levels 14% were significantly associated with a negative fHER2 status, indicating that fHER2 overexpression could be associated with a better clinical outcome.…”
Section: Discussionsupporting
confidence: 88%
“…The pathogenesis and progression of breast cancer have been connected to a number of critical genes, those that control cell division and growth, apoptosis or the ones that repair damaged DNA [ 39 , 40 , 41 ]. The somatic alterations in the genome that result in tumor initiation can be viewed as a disequilibrium in a scale where oncogenes are activated by mutation or copy number gain, and tumor suppressor genes are inactivated by mutation or copy number loss, culminating in an antagonist scenario to that of a normal genome [ 42 , 43 , 44 ].…”
Section: Cat Critical Cancer Genes: a Sequence Perspectivementioning
confidence: 99%
“…From the genes probably involved in cat mammary tumors, some are viewed as critical (highly important for the tumorigenic process) and for that reason great importance has been attributed to them ( Table 1 ). Amongst these, TP53 suppressor gene and growth factor genes, such as the epithelial growth factor receptor family ( EGFR family, mainly the erbB-2 Receptor Tyrosine Kinase 2, usually named ERBB2 , EGFR2 , HER2 or NEU ) (e.g., [ 4 , 39 , 40 , 41 ]), have been the most studied at the sequence level. Some other genes have attracted the attention of researchers, but at a lower level.…”
Section: Cat Critical Cancer Genes: a Sequence Perspectivementioning
confidence: 99%